Multispectral labeling of antibodies with polyfluorophores on a DNA backbone and application in cellular imaging - Guo, Jia (National Academy of Sciences, 2011)
Most current approaches to multiantigen fluorescent imaging require overlaying of multiple images taken with separate filter sets as a result of differing dye excitation requirements. This requirement for false-color composite imaging prevents the user from visualizing multiple species in real time and disallows imaging of rapidly moving specimens. To address this limitation, here we investigate the use of oligodeoxyfluoroside (ODF) fluorophores as labels for antibodies. ODFs are short DNA-like oligomers with fluorophores replacing the DNA bases and can be assembled in many colors with excitation at a single wavelength. A DNA synthesizer was used to construct several short ODFs carrying a terminal alkyne group and having emission maxima of 410–670 nm. We developed a new approach to antibody conjugation, using Huisgen–Sharpless cycloaddition, which was used to react the alkynes on ODFs with azide groups added to secondary antibodies. Multiple ODF-tagged secondary antibodies were then used to mark primary antibodies. The set of antibodies was tested for spectral characteristics in labeling tubulin in HeLa cells and revealed a wide spectrum of colors, ranging from violet-blue to red with excitation through a single filter (340–380 nm). Selected sets of the differently labeled secondary antibodies were then used to simultaneously mark four antigens in fixed cells, using a single image and filter set. We also imaged different surface tumor markers on two live cell lines. Experiments showed that all colors could be visualized simultaneously by eye under the microscope, yielding multicolor images of multiple cellular antigens in real time.